SIRT1 Activator E1231 Alleviates Nonalcoholic Fatty Liver Disease by Regulating Lipid Metabolism - Han, Jiangxue; Li, Shunwang; Wang, Weizhi; Jiang, Xinhai; Liu, Chao; Lei, Lijuan; Li, Yining; Sheng, Ren; Zhang, Yuyan; Wu, Yexiang; Zhang, Jing; Zhang, Yuhao; et al. (Current Issues in Molecular Biology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is one of the most common liver diseases. Silencing information regulator 1 (SIRT1) was demonstrated to modulate cholesterol and lipid metabolism in NAFLD. Here, a novel SIRT1 activator, E1231, was studied for its potential improvement effects on NAFLD. C57BL/6J mice were fed a high-fat and high-cholesterol diet (HFHC) for 40 weeks to create a NAFLD mouse model, and E1231 was administered by oral gavage (50 mg/kg body weight, once/day) for 4 weeks. Liver-related plasma biochemistry parameter tests, Oil Red O staining, and hematoxylin-eosin staining results showed that E1231 treatment ameliorated plasma dyslipidemia, plasma marker levels of liver damage (alanine aminotransferase (ALT) and aspartate aminotransferase (AST)), liver total cholesterol (TC) and triglycerides (TG) contents, and obviously decreased hepatic steatosis score and NAFLD Activity Score (NAS) in the NAFLD mouse model. Western blot results showed that E1231 treatment significantly regulated lipid-metabolism-related protein expression. In particular, E1231 treatment increased SIRT1, PGC-1α, and p-AMPKα protein expression but decreased ACC and SCD-1 protein expression. Additionally, in vitro studies demonstrated that E1231 inhibited lipid accumulation and improved mitochondrial function in free-fatty-acid-challenged hepatocytes, and required SIRT1 activation. In conclusion, this study illustrated that the SIRT1 activator E1231 alleviated HFHC-induced NAFLD development and improved liver injury by regulating the SIRT1-AMPKα pathway, and might be a promising candidate compound for NAFLD treatment.